The Impact of Regulations on Genetically Modifi ed Food Acceptance among Malaysian Food Manufacturers: A Proposed Framework - Hussin, Siti Husmila; Ismail, Risyawati Mohamed (International Review of Management and Marketing, 2016)
The aim of this paper is to conceptually propose the elements that constitute the acceptance of GMF among food industries in Malaysia. One of the crucial elements which imparts the acceptance of GMF is regulatory system which is governed by Malaysian authority bodies. This paper is the outcome of a thorough review of the literature undertaken by previous studies in regards to the regulation of food manufacturers as well as regulation of GMF itself. In this review, those literatures were comprehensively studied and rigorously discussed from the perspective of Malaysian food industry. This paper contributes to law, rule and guideline that have to be complied by Malaysian food industries, especially for the food industry which adapted the use and commercialization of GMF in their operation. The subject of this GMF is relatively new in Malaysia. However, in accordance with the previous studies and support from future direction of the Malaysian government, GMF is a one of the technologies which help food industry to remain competitive in the current global market. Therefore, this paper not only focuses on the rules and regulations of food industry, but it also explores the regulatory system of GMF in Malaysian food industry. Keywords: Genetically Modified Food (GMF), Food Manufacturers, Malaysian Food Industry JEL Classifications: F13, L66